Pendekatan Inovatif untuk Meningkatkan Kepedulian Remaja terhadap Posyandu di Desa Ganti - Hamzah, Farid (Primary Journal of Multidisciplinary Research, 2025)
Youth Posyandu (Integrated Health Service Post for Adolescents) is a vital program aimed at improving adolescent health and well-being. However, its implementation is often hindered by low levels of adolescent participation. This study aims to identify and implement innovative approaches to enhance adolescents' awareness and engagement with Posyandu in Ganti Village, Central Lombok. A participatory approach was employed, integrating educational, interactive, and digital activities that actively involved adolescents. The results indicate that innovative strategies—such as social media-based counseling, the use of health-related mobile applications, and engaging activities like creative competitions and group discussions—significantly increased adolescents’ interest in and awareness of the importance of Posyandu. Additionally, the involvement of community leaders and local health cadres contributed to the program’s success. The study concludes that youth-centered, innovative approaches tailored to adolescent needs and interests can effectively boost their engagement with Posyandu. It is recommended that similar strategies be developed in other regions to support the broader success of youth Posyandu programs.